INVESTMENT IN THE FUTURE. - Chen Baoming (Beijing Review, 2020)
As the new technological revolution advances, existing infrastructure must be digitally reconstructed and information infrastructure constructed in accordance with the developing demand of new-generation information technology. The application of new technologies has played a big part in transforming infrastructure and will become an essential standard for modern infrastructure construction. Second, infrastructure that is transformed by the new information technology and other new technologies, such as smart buildings, smart cities and intelligent transportation.